The Effect Of Giving Ginger Water On Disminore In The VIII Class Of Adolescent Girl At Wahidiyah Junior High Shcool Bandar Lor Village Mojoroto District Kediri City - Agustin, Erda Restiya (Jurnal Midpro, 2021)
Ginger is a rhizome plant that is well-known as a spice and medicine. Ginger comes from Africa, Asia and spread from India to China. Ginger is divided into 3, namely emprit ginger, elephant ginger and red ginger. Each ginger has almost the same content. Ginger has a high content of essential acids which function as an analgesic and can treat dysmenorrhea. Dysmenorrhea is pain during menstruation which is divided into 3 degrees, namely mild dysmenorrhea, moderate dysmenorrhea and severe dysmenorrhea. The purpose of this study was to the effect of giving ginger water on disminore in the VIII class of adolescent girls at Wahidiyah Junior High School Wahidiyah Bandar Lor Village, Mojoroto District, Kediri City. The design of this study used a quasi-experimental design with a pre-test-post-test approach with a sample size of 30 respondents. The independent variable in this study was the administration of ginger water while the dependent variable was dysmenorrhea in class VIII junior high school girls at Wahidiyah, Bandar Lor Village, Mojoroto District, Kediri City. Analysis of the data used is the Chi Square statistical test, with = 0.05. The results of this study showed that before being given ginger water, dysmenorrhea still felt, after being given ginger water, dysmenorrhea disappeared. Based on the statistical test results obtained = 0.000 <0.05, it means that H0 is accepted and Ha is rejected. Based on the results of the research above, there is an the effect of giving ginger water on disminore in the VIII class of adolescent girls at Wahidiyah Junior High School Wahidiyah Bandar Lor Village, Mojoroto District, Kediri City. Ginger water can be given when dysmenorrhea because ginger water is a traditional drink that is safe for consumption for women who are experiencing dysmenorrhea.